Lived curriculum & identité linguistique : discours parallèles but intertwined - Doucerain, Marina (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2009)
AbstractThe author uses an autobiographical approach to reinterpret her memories of being an immigrant and an English language learner and to probe how these memories are intimately involved in the process of becoming a science teacher. This reflexive process of “excavation” (Grumet, 1999) allows the writing of narratives that explore how words and language impact identity formation.